Synthetic Studies toward the C1–C12 Fragment of Amphidinolide U - Ciss, Ismaila; Seck, Matar; Figadère, Bruno; Ferrié, Laurent (Synlett, 2023)
Amphidinolide U is a cytotoxic marine macrolide isolated from Amphidinium sp., sharing 75% of the amphidinolide C backbone. We report here a synthetic study of the C1–C12 fragment of amphidinolide U. The C6–C12 pattern was built using consecutive regioselective ring opening of epoxides, a directed reaction to control newly formed stereogenic centers. In parallel, the C1–C5 moiety was constructed by taking advantage of a symmetrical diol. Attempts to cross-couple the C1–C5 and C6–C12 fragments by using a Suzuki cross-coupling reaction led to poor conversion rates. The same transformation on a close substrate model used during past studies on the total synthesis of amphidinolides F and C2 was successful. These contrasting results could be explained by a presumed steric hindrance of the protecting group adjacent to the vinyl function involved in the cross-coupling reaction. Our investigations will stimulate the optimization of C(sp2)–C(sp3) cross-coupling reactions with bulky substrates, with the aim of achieving a total synthesis of amphidinolide U.
Keywords: amphidinolides; polyketides; total synthesis; Suzuki cross-coupling; epoxides; protecting groups